2014
DOI: 10.2135/cropsci2013.07.0489
|View full text |Cite
|
Sign up to set email alerts
|

Introgressing White Mold Resistance from Phaseolus coccineus PI 439534 to Common Pinto Bean

Abstract: White mold [caused by Sclerotinia sclerotiorum (Lib.) de Bary] is a devastating disease of common bean (Phaseolus vulgaris L.) in cool‐ to moderate‐temperature and wet‐production regions worldwide. Use of resistant cultivars is crucial for effective and economical white mold control. Partial resistance exists in cultivated and wild common bean and Phaseolus species of the secondary gene pool. The objectives were to (i) develop highly resistant breeding lines (BL) from a recurrent interspecific backcross of com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
38
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(44 citation statements)
references
References 55 publications
0
38
0
1
Order By: Relevance
“…G122 is a well-known source of resistance to white mold abroad (Griffiths, 2009;Miklas et al, 2014;Singh et al, 2014;Viteri and Singh, 2015) and recently has been used in breeding programs in Brazil (Carneiro et al, 2011;Carvalho et al, 2013). The physiological resistance present in G122 is controlled by one gene with a predominance of additive effects, which facilitates the use of this line in breeding programs (Carneiro et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…G122 is a well-known source of resistance to white mold abroad (Griffiths, 2009;Miklas et al, 2014;Singh et al, 2014;Viteri and Singh, 2015) and recently has been used in breeding programs in Brazil (Carneiro et al, 2011;Carvalho et al, 2013). The physiological resistance present in G122 is controlled by one gene with a predominance of additive effects, which facilitates the use of this line in breeding programs (Carneiro et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…With regard to the common bean (Phaseolus vulgaris L.), breeding for white mold resistance has advanced recently, especially in the United States, where several studies on the genetic mechanisms of resistance and breeding strategies have been carried out (Terán and Singh, 2009;Terán and Singh, 2010;Singh et al, 2014;Viteri and Singh, 2015) and a number of partially resistant lines have been released (Griffiths, 2009;Kelly et al, 2012;Miklas et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Inheritance studies have shown that partial resistance is quantitative in nature, further complicating the task of resistance breeding (Miklas et al, 2004). For example, resistance sources such as that reported in the 'Ex Rico 23' (also known as ICA Bunsi) navy bean (Tu and Beversdorf, 1982) have over years shown moderate levels of disease avoidance in the field (Kolkman and Kelly, 2002) but fail to show the same moderate levels of resistance in the greenhouse straw test (Singh et al, 2014). For example, resistance sources such as that reported in the 'Ex Rico 23' (also known as ICA Bunsi) navy bean (Tu and Beversdorf, 1982) have over years shown moderate levels of disease avoidance in the field (Kolkman and Kelly, 2002) but fail to show the same moderate levels of resistance in the greenhouse straw test (Singh et al, 2014).…”
mentioning
confidence: 99%
“…Sources of resistance to white mold are highly variable, coming mainly from the Andean gene pool (Schwartz and Singh, 2013), from unadapted landrace and wild relatives (Mkwaila et al, 2011), and from interspecific lines that need prebreeding before introgression into elite germplasm (Singh et al, 2014). In addition, many sources reported to provide high levels of resistance in the greenhouse are very poorly adapted to temperate field conditions.…”
mentioning
confidence: 99%
“…Low levels of white mold resistance (detected in the greenhouse tests) and/or plant architectural avoidance (detected in the field tests) are found in the Middle American cultivated and wild common bean (McCoy et al, 2012; Miklas et al, 2013; Mkwaila et al, 2011; Singh et al, 2014b, 2014c). However, higher levels of resistance occur in the Andean common bean (Maxwell et al, 2007; Miklas et al, 2001a; Singh et al, 2007a, 2014b, 2014c; Viteri et al, 2015) and Phaseolus species of the common bean secondary gene pool such as P. coccineus L., P. polyanthus Greenman (synonymous with P. dumosus ), and P. costaricensis Freytag & Debouck (Gilmore et al, 2002; Miklas et al, 1998; Schwartz et al, 2006; Singh et al, 2009a, 2014c).…”
mentioning
confidence: 99%